2002
DOI: 10.1542/peds.110.6.1103
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Continues to Increase Into the New Millennium

Abstract: If increases in breastfeeding continue at the current rate (approximately 2% per year), in-hospital breastfeeding in the United States should meet or exceed the Healthy People 2010 goal of 75% for the early postpartum period. However, the Healthy People 2010 goal for continued breastfeeding to 5 to 6 months of age (50%) may not be reached in every subgroup. To ensure that these goals are achieved, educational and promotional strategies for breastfeeding must be continued to support mothers who are young, less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
274
9
9

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 391 publications
(317 citation statements)
references
References 42 publications
23
274
9
9
Order By: Relevance
“…In the multivariate analyses we account for these individuals using right censorship. 3 A larger percentage of Asians in the military are Filipino compared to in the civilian population [28] and this is also the case in our data. While we can only speculate, recent research has shown that infant formula lobbying in the Philippines has been linked to lowered breastfeeding rates among Filipino women [29].…”
Section: Dependent Variablessupporting
confidence: 76%
See 2 more Smart Citations
“…In the multivariate analyses we account for these individuals using right censorship. 3 A larger percentage of Asians in the military are Filipino compared to in the civilian population [28] and this is also the case in our data. While we can only speculate, recent research has shown that infant formula lobbying in the Philippines has been linked to lowered breastfeeding rates among Filipino women [29].…”
Section: Dependent Variablessupporting
confidence: 76%
“…Interestingly, Asian mothers in the military are less likely to breastfeed for as long as their civilian counterparts, although this difference disappears at 16 weeks of breastfeeding duration. 3 Independent Variables individuals for whom no data was available because they received the survey before their infant was that old. In the multivariate analyses we account for these individuals using right censorship.…”
Section: Dependent Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further evidence indicates that there may be wide geographical variation in terms of breast-feeding initiation both internationally (49)(50)(51) and in Ireland. As far back as 1986 the highest breast-feeding rates were observed in the Dublin maternity hospitals (43%), while no mother was reported to have breast-fed in Carlow or Dundalk (32) .…”
Section: Regional Variationmentioning
confidence: 99%
“…Higher initiation rates have been documented in large international longitudinal studies, including 69% in 2002 in the UK (64) , 69 . 5% in 2002 in the USA (50) , 88% in 2001 in Australia (65) , 97% in 2004 in Switzerland (66) and 99% in 2003 in Norway (67) .…”
Section: International Comparisons In Breast-feeding Initiation and Dmentioning
confidence: 99%